Measures of exercise intensity during soccer training drills with professional soccer players - Little, T.; Wiliams, A. G. (The Journal of Strength and Conditioning Research, 2007)
Recent evidence supports the use of certain soccer drills for combined technical and physical training. Therefore, it is important to be able to accurately monitor training intensity during soccer drills intended for physical development to allow the optimization of training parameters. Twenty-eight professional soccer players were assessed for heart rate (HR) and rating of perceived exertion (RPE) responses to 5 commonly used soccer training drills (2v2 to 8v8 drills). The responses of both HR and RPE differed significantly (p < 0.05) between the drills, generally showing an elevated response to drills involving lower player numbers. However, the 2v2 drill showed a significantly (p < 0.05) lower HR response (mean +/- SD: 88.7 +/- 1.2% HRmax) than 3v3 (91.2 +/- 1.3% HRmax) and 4v4 drills (90.2 +/- 1.6% HRmax). There was no significant correlation between the HR and RPE responses to the various drills (r = 0.60, p < 0.200). This poor relationship is probably because during the 2v2 drill, RPE was higher than during any of the other 6 drills, whereas HR was only fourth highest of the 6 drills. This demonstrates that HR and RPE are only poorly related during the intense drills used in this study, and that HR underestimates the intensity of the 2v2 drill. Heart rate demonstrated lower intersubject variability (1.3-2.2%) than RPE (5.1-9.9%). However, unlike HR, Borg 15-point RPE appears to be a valid marker of exercise intensity over a wide range of soccer training drills by maintaining validity in all drills and demonstrating acceptable intersubject variability. A combination of both HR- and RPE-based training load calculations appears optimal for use in soccer training.